Political Economy of the Petroleum Sector in Nigeria - Gboyega, Alex (2012)
The relatively slow pace of Nigeria's development has often been attributed to the phenomenon of the resource curse whereby the nature of the state as a "rentier" dilutes accountability for development and political actors are able to manipulate institutions to sustain poor governance. The impact of the political elite's resource-control and allocation of revenues on core democratic mechanisms is central to understand the obstacles to development and governance failure. Given that problems of petroleum sector governance are extremely entrenched in Nigeria, the key question is whether and how it is possible to get out of a poor equilibrium after fifty years of oil production. This paper uses a political economy perspective to analyze the governance weaknesses along the petroleum sector value chain and attempts to establish the links between challenges in sector regulation and the following major political and economic attributes: (i) strong executive control on petroleum governance in a political environment of weak checks and balances; (ii) regulatory and operating roles bundled into one institution, thereby creating conflict of interest; and (iii) manipulation of elections and political appointments. The restoration of democratic government has helped improve transparency and management of oil revenue and reforms at the federal level and proposed reforms of the petroleum sector hold much promise. At the same time, the judiciary has started to restore confidence that it will serve as a check and balance on the executive and the electoral process. Yet, these reforms are fragile and need to be deepened and institutionalized. They must be addressed not as purely technocratic matters but as issues of political economy and vested interests that must, through regulation and reform, be aligned with the public interest and a vision of Nigerian development.